Prevalence and Predictors Associated to Schistosoma mansoni Infection among Patients Attending the Saint Jean de Malte Hospital, Njombe, Littoral Region, Cameroon - Ambe Fabrice Ngwa; Pride Tanyi Bobga; Ekwi Damian Nsongmayi; Gedeon Schadrack Yememe Yememe; Judith Ngong Nyeme; Mohamed Isah; Ebai Christabel Ashu; Calvin Bisong Ebai (Journal of Parasitology Research)
Background. Schistosomiasis remains a major public health concern in sub-Saharan Africa. It has been associated to morbidity and mortality in developing countries including Cameroon, and Njombe-Penja health district is an endemic area. This study is aimed at determining the prevalence and risk factors of Schistosoma mansoni infection among patients attending the Saint Jean de Malte Hospital, Njombe. Methods. A cross-sectional study design was employed, with the enrolment of 300 participants using convenience sampling technique. Data were collected using a structured questionnaire. Stool specimens were collected and examined using direct microscopy, Kato-Katz’s method, and formol ether concentration technique. Data were analyzed using SPSS, and chi-square test was used to assess the association. Risk factors for S. mansoni infection were assessed using multivariable logistic regression, and a p<0.05 was considered significant. Results. The overall prevalence of Schistosoma mansoni infection was 13%. Schistosoma mansoni infection was mostly frequent among patients<20 years and males. Stream usage (AOR=2.15, 95% CI. 1.32–3.50), always visiting the stream (AOR=11.35, 95% CI 2.33-55.33), always swimming and washing clothes in the stream (AOR=7:10, 95% CI 2.31-21.80), age group < 20 years (AOR=3.7, 95% CI 1.1-12.2), and age group 20-29 years (AOR=2.58, 95% CI 1.14-18.42) were significantly associated with increased risk of S. mansoni infection. Conclusion. These findings suggest that Schistosoma mansoni infection is of public health concern in Njombe and its environs. Age of <20 years and between 20 and 29 years, stream usage, always visiting the stream, and always swimming and washing clothes in the stream were the main risk factors of S. mansoni infection. Thus, mass drug administration and health education are required.